Magnetic fields in star-forming systems - II: Examining dust polarization, the Zeeman effect, and the Faraday rotation measure as magnetic field tracers - Reißl, Stefan; Stutz, Amelia M.; Klessen, Ralf S.; Seifried, Daniel; Walch, Stefanie (Monthly notices of the Royal Astronomical Society, 2021)
The degree to which the formation and evolution of clouds and filaments in the interstellar medium is regulated by magnetic fields remains an open question. Yet the fundamental properties of the fields (strength and 3D morphology) are not readily observable. We investigate the potential for recovering magnetic field information from dust polarization, the Zeeman effect, and the Faraday rotation measure (RM) in a SILCC-Zoom magnetohydrodynamic (MHD) filament simulation. The object is analysed at the onset of star formation and it is characterized by a line-mass of about $\mathrm{\left(M/L\right) \sim 63\ M_{\odot }\ pc^{-1}}$ out to a radius of $1\,$ pc and a kinked 3D magnetic field morphology. We generate synthetic observations via polaris radiative transfer (RT) post-processing and compare with an analytical model of helical or kinked field morphology to help interpreting the inferred observational signatures. We show that the tracer signals originate close to the filament spine. We find regions along the filament where the angular dependence with the line of sight (LOS) is the dominant factor and dust polarization may trace the underlying kinked magnetic field morphology. We also find that reversals in the recovered magnetic field direction are not unambiguously associated to any particular morphology. Other physical parameters, such as density or temperature, are relevant and sometimes dominant compared to the magnetic field structure in modulating the observed signal. We demonstrate that the Zeeman effect and the RM recover the line-of-sight magnetic field strength to within a factor 2.1-3.4. We conclude that the magnetic field morphology may not be unambiguously determined in low-mass systems by observations of dust polarization, Zeeman effect, or RM, whereas the field strengths can be reliably recovered.
Published online: 2020 May 4
Gesehen am 12.02.2021